Novel Butane-Oxidizing Bacteria and Diversity of bmoX Genes in Puguang Gas Field - Deng, Yue; Deng, Chunping; Yang, Jinshui; Li, Baozhen; Wang, Entao; Yuan, Hongli (Frontiers in Microbiology, 2018)
To investigate the diversity of butane oxidizing bacteria in soils contaminated by long-term light hydrocarbon microseepage and the influence of butane on the soil microbial community, a quantitative study and identification of butane-oxidizing bacteria in soils at the Puguang gas field were performed by DNA-based stable isotope probing (DNA-SIP). For the first time, two phylotypes corresponding to the genera Giesbergeria and Ramlibacter were identified as being directly involved in butane oxidation, in addition to the well-known light hydrocarbon degrader Pseudomonas. Furthermore, bmoX genes were strongly labeled by 13C-butane, and their abundances in gas field soils increased by 43.14-fold, 17.39-fold, 21.74-fold and 30.14-fold when incubated with butane for 6, 9, 12 and 14 days, respectively, indicating that these bmoX-harboring bacteria could use butane as the sole carbon and energy source and they play an important role in butane degradation. We also found that the addition of butane rapidly shaped the bacterial community and reduced the diversity of bmoX genes in the gas field soils. These findings improve our understanding of butane-oxidizing bacteria in the gas field environment and reveal the potential for their applications in petroleum exploration and bioremediation.